Which is responsible for target organ damage in masked hypertension? Is it an increase in blood pressure or a disruption of the circadian rhythm? - Ertan Akbay; Ali Çoner; Sinan Akıncı; Ali Rıza Demir; Aydın Toktamiş (Clinical and Experimental Hypertension, 2021)
Objective Masked hypertension (MH) and non-dipping pattern are conditions associated with target organ damage and cardiovascular risk, which are frequently observed together. We aimed to show the relationship between the target organ damage observed in MH and the deterioration in the dipping pattern. Methods Patients who underwent ambulatory blood pressure monitoring (ABPM) and office blood pressure (BP) <140/90 mmHg were retrospectively screened. In ABPM data, those with daytime BP ≥135/85 mmHg and night BP ≥120/70 mmHg were included in the MH group, while the others were included in the normotensive group. The patients were grouped as dipper, non-dipper and reverse-dipper according to ABPM results. Left ventricular mass index (LVMI), glomerular filtration rate (GFR) and serum creatinine levels were used to determine target organ damage. Results 289 patients [mean age 46.6 ± 12.4 years, 136 (47.1%) males], 154 (53.3%) of whom had MH were included in our study. GFR value was found to be significantly lower, serum creatinine levels and LVMI were significantly higher in patients with MH compared to normotensives (p < .05, for all). When the subgroups were examined, it was found that this difference was associated with the disruption in the dipping pattern. In patients with MH, dipping pattern disruption without change in systolic BP was independently associated with an increase in LVMI (p < .05, for both). Conclusion Target organ damage seen in MH may be due to the deterioration of the dipping pattern.